2011
DOI: 10.1590/s1809-29502011000200005
|View full text |Cite
|
Sign up to set email alerts
|

Análise do equilíbrio estático e de deformidades nos pés de crianças com paralisia cerebral

Abstract: Aprovação do Comitê de Ética em Pesquisa (CEP) da FFC UNESP com parecer favorável número 3762/2008. RESUMO: O presente estudo analisou, por meio de um sistema de baropodometria, os tipos de pé, a influência da visão no equilíbrio estático na postura ortostática e a distribuição da pressão plantar em 16 crianças, de 6 a 15 anos, com diagnóstico de paralisia cerebral. Os resultados indicaram que o pé valgo foi o mais comum dentre os tipos de paralisia cerebral estudadas, diparesia espástica, hemiparesia espástic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
2
4
0
1
Order By: Relevance
“…(25) agreeing with our findings, Costa et al, (10) using the baropodometry system, found that the flat foot was the most common in the evaluated 16 CPs aged 6 to 15 years. It is important to remember that the age variation in our study was shorter (three to eight years) and that up to three years of age, the child's foot has a greater degree of mobility than the adult foot, as a consequence of a greater peculiar ligament elasticity in the early life.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…(25) agreeing with our findings, Costa et al, (10) using the baropodometry system, found that the flat foot was the most common in the evaluated 16 CPs aged 6 to 15 years. It is important to remember that the age variation in our study was shorter (three to eight years) and that up to three years of age, the child's foot has a greater degree of mobility than the adult foot, as a consequence of a greater peculiar ligament elasticity in the early life.…”
Section: Discussionsupporting
confidence: 93%
“…This time was established because they are children with difficulty to remain in static posture for a long time. (10) Each record was repeated three times, for greater reliability, (11) with an interval of 10 seconds and it was considered the average of the three collections for analysis.…”
Section: Methodsmentioning
confidence: 99%
“…There was a prevalence of the flat foot among children with CP, in concordance with the results by Galli et al 10 and Costa et al 1 , in which all the studied CP topographies registered the predominance of flat foot. Such a finding can be justified by the increase of anterior weight-bearing presented by the children evaluated in this study.…”
Section: Discussionsupporting
confidence: 91%
“…Cerebral Palsy (CP) is characterized as movement and posture disorders, consequential of non-progressive afflictions in the developing encephalon, which causes performance limitations in activities easily performed by children with typical development (TD) 1,2 . Abnormalities in muscle tone and, consequently, in posture, are common in children with CP, spasticity being the most 2 predominant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation